Tucker - March, Emily (March, Emily. McBrides of Texas., 2020)
Meet Gillian Thacker. Her business: Bliss Bridal Salon. Her passion: Weddings. Her own wedding: It<U+2019>s complicated. Life isn<U+2019>t turning out like she<U+2019>d planned. The last thing she wants is for a real-life hero to ride to her rescue when an unexpected event puts her entire future in Redemption, Texas, at risk. So what<U+2019>s a broken-hearted bridal expert to do? Maybe a new set of survival skills is exactly what she needs<U+2026> Tucker McBride has been proud to call himself a U.S. Army Ranger. But now that his days of service are over, he<U+2019>s decided to put his expertise to use by founding a wilderness skills training school. He sets up shop in Redemption, next to Bliss Bridal, and so begins life: Part Two. Marriage has been pretty low on his agenda, but as soon as he meets Gillian, Tucker can<U+2019>t help but contemplate the ultimate challenge: Convincing the reluctant bride to take his hand and leap into the adventure of a lifetime. . .until death do they part.